Assessing the knowledge, attitude, and practice of frontline physicians in Egyptian university hospitals regarding pharyngitis and acute rheumatic fever: a cross-sectional study that calls for action - Kerollos Abdelsayed; Hossam Tharwat Ali; Mohamed Basyouni Helal; Ahmed Assar; Maysa Madany; Mohamed Diaa Gabra; Ahmed Abdelrahman; Yomna Goudy; Ahmed Dandrawy; Ziad Ashraf Soliman; Heba M. Qubaisy; Ghada. M. M. Shahin; et al. (BMC, 2024)
Abstract Background Acute rheumatic fever (ARF) and rheumatic heart disease (RHD) remain major public health issues. Although the primary and secondary prevention of RHD through appropriate management of bacterial pharyngitis and ARF are well-described in the literature, few studies address the knowledge, attitude, and practice (KAP) of developing countries. We aimed to evaluate the KAP of the frontline physicians in Egyptian university hospitals regarding pharyngitis and ARF. Methods We employed a cross-sectional design between September 1st, 2022, and January 31st, 2023 using a self-administered questionnaire in 21 Egyptian universities. The questionnaire was developed based on previous studies and recent guidelines and included four domains: sociodemographic data, knowledge, attitude, and practice regarding pharyngitis and ARF. We utilized both online (Google Forms) and paper surveys. Frontline physicians, including interns, residents, and assistant lecturers, were conveniently invited to participate. Furthermore, with the help of participating phycisians in recruiting their colleagues, we utilized the snowball method. Data were analyzed using IBM SPSS version 27 software. Results The final analysis included 629 participants, of whom 372 (59.1%) were males and 257 (40.9%) had direct contact with ARF patients. Most participants (61.5%) had a fair knowledge level while 69.5% had a fair level of practice regarding ARF and pharyngitis. Higher satisfactory knowledge levels were noted regarding pharyngitis (17.1% vs. 11.3%; p-value: 0.036) and ARF (26.8% vs. 18%; p-value: 0.008) among physicians dealing directly with ARF cases compared to physicians in departments not dealing directly with ARF cases. Physicians in Cairo region universities had significantly higher levels of satisfactory knowledge about ARF compared to Delta and Upper Egypt region universities (p = 0.014). Delta region universities showed significantly lower levels of practice compared to Cairo and Upper Egypt region universities (p = 0.027). The most frequently recognized barriers against health promotion were low socioeconomic status (90.3%) and lack of adequate public education (85.8%). Conclusions Despite the fair knowledge and practice levels towards bacterial pharyngitis and ARF among participants, many gaps were still identified that might contribute to RHD prevalence. Educational interventions should be implemented by updating the local guidelines in Egypt for diagnosis and management based on the most recent guidelines.